Pattern of segmental motor involvement in syringomyelia: a single fibre EMG study. Issue 2 (February 1980) - Schwartz, M S; Stålberg, E; Swash, M
Abstract : Single fibre EMG has been used to study the pattern of upper limb motor involvement in syringomyelia. Biceps brachii, extensor digitorum communis (EDC) and first dorsal interosseous muscles (1stDI) representing C5/6, C7/8 and C8/T1 segments, were studied. In the biceps the fibre density was slightly increased in most patients, in EDC it was about twice the normal and in the 1stDI it was about three times normal. The potentials were least stable and of longest duration in the 1stDI. These findings seem to indicate a relatively constant pattern of involvement of anterior horn cells in the brachial segments in syringomyelia.